ATTITUDES OF GEORGIAN CONSUMERS TOWARDS CORPORATE SOCIAL RESPONSIBILITY - Gigauri, Iza (European Scientific Journal, ESJ, 2012)
Corporate social responsibility (CSR) increasingly receives attention from researchers, especially in the area of consumer perception. But most studies were conducted in the developed countries. This research in Georgia demonstrates that research on consumer perception towards CSR as well as on CSR generally needs to be pursued in developing countries. Georgian consumers are less aware about CSR, nevertheless, they demand more information about it, and there is a strong tendency that consumers will support the CSR programs in case of appropriate marketing strategies.